Insecticide Use Pattern on Tomato Crop in Punjab - Ravinder Singh Chandi; Anureet Kaur Chand (Indian Journal of Extension Education, 2014)
Tomato is one of the important, popular and remunerative vegetable crops grown around the world for fresh market and processing. Fruit borer, Helicoverpa armigera (Hubner) is rated as one of the most noxious pests infesting tomato crop. Overuse of insecticide to knock down this destructive pest has led to many problems like build up of insecticide resistance, resurgence, replacement of natural enemies and insecticide residue in tomato fruits. The vegetable growers, therefore, are using a wide range of insecticides, either single or in mixtures for its control. Out of the six insecticides viz. flubendiamide, profenophos, carbaryl, cypermethrin, deltamethrin, and fenvalerate recommended by Punjab Agricultural University, Ludhiana for its control, carbaryl was not being used by the farmers. Fourteen insecticides singly and two mixtures were being used extensively by the vegetable growers of the state. On an average, 3.87 sprays (range 3-8 sprays) were done by each tomato grower. Out of these, 29.97 per cent sprays were done with recommended insecticides, 56.31 per cent with unrecommended insecticides and 13.69 with unrecommended mixtures. Chlorantraniliprole 18.5 SL, being unrecommended was used to a tune of 17.31 per cent, while flubendiamide 480 SC (10.59%) lead in recommended insecticides. Cypermethrin and chlorpyriphos were the most frequently used mixtures.